INVESTIGASI PARAMETER PENGELASAN SMAW PADA STST. 304 UNTUK KEKUATAN TEKUK OPTIMAL DENGAN TAGUCHI-GRA - Kristian Ismartaya; Dan Daniel Pandapotan; Yosua Kusuma Negara; Gilang Argya Dyaksa; Ronald Sukwadi (Fakultas Teknologi Lingkungan dan Mineral - Universitas Teknologi Sumbawa, 2025)
Mechanical strength in weld joints is important in construction strength. This research takes the issue of SMAW weld joints strength when receiving bending loads on hopper products made from stainless steel 304. Two types of bending loads identified: root bend and face bend load. This research aims to obtain welding process parameters that are able to maximize the bending strength value of SMAW welding joints on stainless steel 304 material. Taguchi's experimental design uses current strength factors and electrode diameter, with an L8 (4121) Orthogonal Array. The novelty of this research is the use of response variables for root bend and face bend strength values which are optimized simultaneously. Multi-response optimization using Grey Relational Analysis method. The results of multi-response optimization are applied in confirmation tests to obtain actual results. The combination of a current strength of 65 A and an electrode diameter of 2.6 mm produces an optimal bending strength value with a desirability of 0.7475. These parameters produce actual face bend strength response of 1071.01 MPa (an increase of 5.38%) and a root bend strength of 1065.86 MPa (an increase of 17.36%).